Evaluación del consumo y calidad del agua en el proceso de curtido en la industria del cuero en la empresa ecuatoriana de curtidos Salazar s.a, provincia de Cotopaxi, cantón Salcedo, período 2014-2015 - Cóndor Basantes, Erika Elizabeth (2016)
The goal was to evaluate the levels of consumption and water quality in the tanning process in the Ecuadorian Company tannery Salazar SA, and characterize the process, to propound techniques about water optimization. They were defining inputs, outputs, suppliers, users, requirements, indicators, documentation and risks. The sampling points are located in the deposit reservoir tank, mouth hype, treatment plant and output to body receiver. The quality of water into the process was estimated as excellent, because it remains in a natural condition. The direct affluent of the process is characterized as heavily polluted....